The Symbolic Meaning of Communication in Rudat Dance Art: A Study of the Paleben Group in Subang Village, Kuningan Regency - Sugiarta, Nugraha; Hanafi, Hanafi; Lestari, Anggita; Reza, Faisal; Ikbal, Dadan Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The art of rudat dance is one of the arts from Subang Village, Kuningan Regency. Rudat is a type of art in which there is a dance accompanied by tambourine clapping where the dance elements contain elements of martial arts. The aim of this research is to find out the forms of communication symbols in rudat dance art in Subang Village, Kuningan Regency, and to find out the performers of rudat dance art in interpreting rudat dance art. The research method used is qualitative with a symbolic interaction study approach. Data was obtained based on interviews and observations. Data processing and data analysis techniques use the data analysis model of Miles and Huberman. The results obtained from this research are: First, the forms of symbols in rudat art are from the basic rudat dance movements. There are four symbols used, namely the Gojes symbol in a stance with the right hand directed to the left, the left hand positioned behind the body and has the meaning of preparing oneself for what is to come. The Kincar Symbol is in an attacking position, the right hand extended forward with the fingers clenched into a fist, and the left hand bent with the fingers clenched into a fist, which has the meaning of facing existing problems. The Alayya symbol with the body moving sideways to the right and left has the meaning of avoiding something bad. And finally, the Ogel symbol in a defensive position. The right hand, which is positioned to protect the chest, and the left hand holding the right arm, has the meaning of surviving all trials. The two rudat dancers want to preserve rudat art so that the people in Subang Village, Kuningan Regency don’t forget it by performing rudat dance performances regularly.